Thermal Behavior of Rhabdophanes(LnPO4·nH2O) and Chemical Stability of Their Phase Transition Products - ZHENG Xia-yu; ZHAO Xiao-feng; TENG Yuan-cheng; LIU Hang; HU Qi (He huaxue yu fangshe huaxue, 2023)
LnPO4·nH2O rhabdophane is considered as one of potential material for precipitation-enrichment actinides in high-level radioactive waste liquid owing to its outstanding properties relating to the high chemical stability and the high selectivity and strong incorporating capacity of actinides. In this work, the phase composition, microstructure and thermal behaviors of LnPO4·0.667H2O(Ln=La, Eu, Gd) were systematically investigated by combining with XRD, SEM, TG-DSC, BET and ICP-MS. Based on the PCT leaching test methods, the differences of chemical stability between LnPO4·0.667H2O and its thermal products were first discussed in detail. The results reveal that the single phase of LnPO4·0.667H2O(Ln=La, Eu, Gd) with the microstructure of hexagonal shaped nanorodcrystals can be synthesized by chemical precipitation reaction in 90 ℃ aqueous solution. LnPO4·0.667H2O has the excellent structural stability and the reversibility behaviors associated with dehydration and adsorption of water molecules. The process of phase transition can be described as: LnPO4·0.667H2O25-80 ℃LnPO4·0.5H2O80.240 ℃LnPO4(rhabdophane)661-935 ℃LnPO4(monazite). Moreover, the excellent chemical stability has been observed in LnPO4·0.667H2O rhabdophane and its thermal products in PCT leaching test. For instance, the values of LRLn are ranged from 10-7 g/(m2·d) to 10-4 g/(m2·d) after leaching 28 d in different leaching solutions(pH=3/7, T=90/150 ℃), where the acidic solution is more likely to corrode sample surface, further resulting in a relative high LRLn value. Importantly, the phase transition can improve the chemical stability of initial rhabdophane. As a typical example of Gd-rhabdophane, after leaching 28 d in 90 ℃/pH=3 solutions, the evolution of chemical stability is found as: GdPO4·0.667H2O(1.8×10-4 g/(m2·d))<GdPO4·nH2O(0<n<0.667, 6.4×10-5 g/(m2·d))<Gd-monazite(1.2×10-5 g/(m2·d)). Furthermore, a relative smaller influence on stability of changing temperature has been observed comparing to pH impaction.